Evidence for Mitochondrial Genome Methylation in the Yeast Candida albicans: A Potential Novel Epigenetic Mechanism Affecting Adaptation and Pathogenicity? - Bartelli, Thais F.; Bruno, Danielle C. F.; Briones, Marcelo R. S. (Frontiers in Genetics, 2018)
The commensal yeast Candida albicans is an opportunistic pathogen. In order to successfully colonize or infect the human body, the fungus must adapt to the host’s environmental conditions, such as low oxygen tension (hypoxia), temperature (37°C) and the different carbon sources available. Previous studies demonstrated the adaptive importance of C. albicans genetic variability for its pathogenicity, although the contributions of epigenetic and the influence of environmental factors are not fully understood. Mitochondria play important roles in fungal energetic metabolism, regulation of nuclear epigenetic mechanisms and pathogenicity. However, the specific impact of inter-strain mitochondrial genome variability and mitochondrial epigenetics in pathogenicity is unclear. Here we draw attention to this relevant organelle and its potential role in C. albicans pathogenicity and provide preliminary evidence, for the first time, for methylation of the yeast mitochondrial genome. Our results indicate that environmental conditions, such as continuous exposure for 12 weeks to hypoxia and 37°C, decrease the mitochondrial genome methylation in strains SC5314 and L757. However, the methylation decrease is quantitatively different in specific genome positions when strains SC5314 and L757 are compared. We hypothesize that this phenomenon can be promising for future research to understand how physical factors of the host affect the C. albicans mitochondrial genome and its possible impact on adaptation and pathogenicity.